REFLECTIONS FOR A BUDDHIST GEOGRAPHY (Brazilian Geographical Journal, 2019)
The expanding contact between western and eastern cultures is helping certain academic disciplines (such as geography) that are based on western philosophies to have a deeper dialogue with eastern philosophies, such as Buddhism. This paper focuses on the Buddhist principles of the Theravada school and their similarities and differences with western doctrines in the academic field of geography. The principles discussed include the following: (1) detachment as a way to escape from suffering; (2) the causal chain (karma) as a world conception in which there is no place for free will; (3) the doctrine of no-self; (4) integrated practice, reflection and compassion in Buddhist ethics; and (5) the nonexclusive and non-proselytizing nature of Buddhism. This discussion opens the way for new developments in the manner in which geography interprets the world and helps people in their lives.